Entrepreneurial finance : - Rogers, Steven (McGraw-Hill, 2009)
Entrepreneurial Finance provides the essential tools and know-how you need to build a sturdy foundation for a profitable business. This practical road map guides you from crafting a meaningful business plan to raising your business to the next level. It offers potent methods for keeping firm financial control of your enterprise and insightful tips for avoiding the multitude of financial barriers that may block your entrepreneurial dream.